1995
DOI: 10.1210/endo.136.6.7750457
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 4, interferon-gamma, and prostaglandin E impact the osteoclastic cell-forming potential of murine bone marrow macrophages.

Abstract: Interleukin 4 (IL-4) is an immune cytokine that inhibits bone resorption in mice and suppresses osteoclastic cell formation in vitro through an undefined mechanism. In this report, we have established the cellular identity of the IL-4 target cell using a variety of bone marrow/stromal cell coculture methods. Initially, we found that the majority of IL-4's inhibition of osteoclastic cell formation was due to its effect on bone marrow cells, not stromal cells. Consequently, bone marrow macrophages were used as o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
34
1
3

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 35 publications
3
34
1
3
Order By: Relevance
“…The levels of osteoclast precursors contained in OPG −/− or wild-type bone marrow and spleen cells were found to be similar when measured by an in vitro osteoclast-forming assay (Lacey et al 1995; data not shown). This finding suggests that the osteoporosis in OPG −/− mice is most likely due to dysregulated osteoclast recruitment and activation in vivo rather than alterations in the number of osteoclast precursors.…”
Section: Resultsmentioning
confidence: 80%
“…The levels of osteoclast precursors contained in OPG −/− or wild-type bone marrow and spleen cells were found to be similar when measured by an in vitro osteoclast-forming assay (Lacey et al 1995; data not shown). This finding suggests that the osteoporosis in OPG −/− mice is most likely due to dysregulated osteoclast recruitment and activation in vivo rather than alterations in the number of osteoclast precursors.…”
Section: Resultsmentioning
confidence: 80%
“…Most strikingly, a consistent signal towards Th2 differentiation was observed with increased expression of IL-4 in the LNs of hTNFtg mice suggesting a shift from the Th17 to the Th2 linage. This is interesting, as IL-4 is one of the most potent suppressors of osteoclast formation [25]. IL-4 inhibits osteoclast differentiation through directly activating PPARg [26], which is a potent transcriptional suppressor for osteoclast differentiation [27].…”
mentioning
confidence: 99%
“…Alguns autores 7,10,12 afirmam que o INF-γ poderia suprimir a formação de osteoclastos por atuar em um período precoce de sua diferenciação. Choi e Kim 4 reforçaram essa afirmativa, ao assegurarem que o INF-γ atuaria diretamente sobre a FIGURA 3 -Representação esquemática das áreas periodontais demarcadas para análise microscópica: (A) área de pressão e (B) área de tração da raiz mesial do 1MS.…”
Section: Discussionunclassified
“…Citocinas como INF-γ e IL-4 podem suprimir a formação de osteoclastos, por atuarem sobre suas células precursoras -os macrófagos da medula ós-sea 12 . De acordo com Fox e Chambers 7 , o INF-γ evita a formação de osteoclastos por atuar diretamente na diferenciação de suas células progenitoras, levando-as à morte celular.…”
unclassified
See 1 more Smart Citation